P Pembinaan Karakter Islami Anak melalui Optimalisasi Magrib Mengaji pada Program Kuliah Kerja Nyata UIN Sumatera Utara Ling. IX Sido Mukti Baru. Kab.Langkat - Rohma Mitra; Ahmad Ramadan Salim Rambe; Khairani Mardatillah; Mhd. Zidni 'Ilman; Kusmilawaty Kusmilawaty (Jurnal Recoms, 2025)
The Revitalization of Maghrib Reading through the Community Service Program (KKN) at UIN Sumatera Utara is a strategic effort to reinforce religious practices that serve as a medium for nurturing Islamic character in children. This study aims to develop and optimize the implementation of Maghrib Reading in the IX Sido Mukti Baru area, Langkat Regency, involving KKN students as implementing partners. The background of this research is based on the decline in children's participation in Maghrib Reading activities due to the influence of technological developments and changes in community lifestyle patterns. The research methodology uses a qualitative descriptive approach with participatory observation, interviews, focused group discussions (FGD), and documentation techniques. Data analysis is conducted through stages of data reduction, data presentation, and conclusion verification. The research results indicate a significant increase in children's participation and the quality of Maghrib Mengaji implementation after the KKN program was carried out. This activity not only strengthens the skills of reading the Qur'an but also fosters Islamic values in children such as discipline, responsibility, politeness, and togetherness. These findings provide important insights into the role of students in supporting religious revitalization and also demonstrate the positive contributions of the KKN program to community development. This study is expected to serve as a model for other mosques in revitalizing community-based religious activities through collaboration with higher education institutions.